(untitled) (Journal of Renal and Hepatic Disorders, 2025)
With the advent of sophisticated non-invasive assays and advanced radiologic techniques, there has been a significant evolution in the role of liver biopsy in the evaluation and management of hepatic diseases. Liver biopsy has a vital role in establishing the diagnosis, staging and prognostic evaluation of various pediatric liver diseases. It is an essential tool in deciding therapeutic management and treatment response. Liver biopsy when used in combination with clinical findings and other diagnostic modalities is useful in guiding treatment and predicting prognosis in the pediatric population. Here we discuss the indications of liver biopsy in various common pediatric liver diseases.